1989
DOI: 10.1007/bf00155038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and electrophysiological findings in three patients with toluene dependency

Abstract: We recorded the electrophysiological findings of three patients with toluene dependency who developed visual disturbance. In five of six eyes the peak latency of the pattern visual evoked cortical potential was prolonged as compared with that of normal subjects. The amplitude and the latency of the a-wave of the electroretinogram were decreased in five of the six eyes and prolonged in four. Those of the b-wave in patients were less affected than the a-wave: in one of six eyes the amplitude of the b-wave was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…However, the severely decreased visual acuity and highly constricted visual field in both eyes do not agree with our diagnosis of peripheral cone dystrophy. These contradictory findings might be because our patient had psychogenic disorders induced by thinner sniffing and the possibility of unilaterally pronounced toxic effects cannot be denied [11]. But thinner sniffing has been reported to lead to mainly optic neuropathy [12, 13] but the normal visual evoked potentials of our patient indicated that this was not likely.…”
Section: Discussionmentioning
confidence: 66%
“…However, the severely decreased visual acuity and highly constricted visual field in both eyes do not agree with our diagnosis of peripheral cone dystrophy. These contradictory findings might be because our patient had psychogenic disorders induced by thinner sniffing and the possibility of unilaterally pronounced toxic effects cannot be denied [11]. But thinner sniffing has been reported to lead to mainly optic neuropathy [12, 13] but the normal visual evoked potentials of our patient indicated that this was not likely.…”
Section: Discussionmentioning
confidence: 66%
“…Cavalleri et al (25) y Campagna et al (26) refieren que la discromatopsia tipo III refleja posibles cambios en las capas externas de la retina. Muttray et al (28) informan que existen estudios que sugieren que el efecto tóxico del tolueno existente en personas con un gran abuso de esta sustancia (ej: inhalación de pegamento) puede producirse en cualquier parte de la vía visual, incluyendo la parte distal y el epitelio pigmentario de la retina (36,37) y concluyen que un efecto tóxico del tolueno en la retina parece posible, pero esta hipótesis no puede ser probada en base a los datos disponibles.…”
Section: Resultados Relacionados Con Efectos En La Visiónunclassified
“…This typically leads to a slow progressive decline in visual acuity ranging from 20/20 to 4/ 200 with associated diminished color vision in most patients [6,14,15]. Initial optic disc appearance is usually normal, but patients gradually develop optic atrophy.…”
Section: Discussionmentioning
confidence: 96%
“…Initial optic disc appearance is usually normal, but patients gradually develop optic atrophy. Visual fields reveal enlargement of the blind spot and central depression [6,14]. Treatment with vitamins, steroids, gabapentin, or cessation of toluene exposure revealed an improvement in visual acuity and symptoms in about half of patients [6,10].…”
Section: Discussionmentioning
confidence: 97%